Seismic Hazard Assessment of Peshawar Basin using Probabilistic Approach - Khawaja, Azam A.; MonaLisa (Journal of Himalayan Earth Sciences, 2002)
The area of Peshawar Basin has been divided into grids of 0.15ox 0.15o size for carrying out seismic hazard assessment by using probabilistic approach. Available instrumental data 24.5for the period of 1905-1998 has been used. Peak Ground Acceleration (PGA) values have been determined for the midpoints of each grid applying attenuation equation of the Public Works Research Institute of Japan (1990) for the return periods of 50 and years. ERISA-P software has been used for calculating the PGA's, Contour maps have been prepared for these different return periods of 50 and 100 years and are discussed taking into consideration the geology of the area.